Slide14.JPG

Slide15.JPG
Slide16.JPG

Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class


Transcript

Misc 8 Solve the differential equation 𝑦 𝑒^(π‘₯/𝑦) 𝑑π‘₯= (𝑒^(π‘₯/𝑦)+𝑦^2 )𝑑𝑦 (𝑦≠0)𝑦 𝑒^(π‘₯/𝑦) 𝑑π‘₯= (𝑒^(π‘₯/𝑦)+𝑦^2 )𝑑𝑦 𝒅𝒙/π’…π’š = (𝒙𝒆^(𝒙/π’š) + π’š^𝟐)/(π’š^(𝒆^(𝒙/π’š) ) ) We can see that it is not homogeneous, so let’s try something else 𝑦𝑒^(π‘₯/𝑦) 𝑑π‘₯/𝑑𝑦=π‘₯𝑒^(π‘₯/𝑦)+𝑦^2 𝑦𝑒^(π‘₯/𝑦) 𝑑π‘₯/π‘‘π‘¦βˆ’π‘₯𝑒^(π‘₯/𝑦)=𝑦^2 𝑒^(π‘₯/𝑦) (𝑦 𝑑π‘₯/π‘‘π‘¦βˆ’π‘₯)=𝑦^2 𝒆^(𝒙/π’š) ((π’š 𝒅𝒙/π’…π’š βˆ’ 𝒙)/π’š^𝟐 )=π’š^𝟐 Let 𝒆^(𝒙/π’š) = z Diff w.r.t. y. 𝑒^(π‘₯/𝑦) 𝑑(π‘₯/𝑦)/𝑑𝑦 = 𝑑𝑧/𝑑𝑦 𝑒^(π‘₯/𝑦) ((𝑦 𝑑π‘₯/𝑑𝑦 βˆ’ π‘₯ 𝑑𝑦/𝑑𝑦)/𝑦^2 )=𝑑𝑧/𝑑𝑦 " " 𝒆^(𝒙/π’š) ((π’š 𝒅𝒙/π’…π’š βˆ’ 𝒙)/π’š^𝟐 )=𝒅𝒛/π’…π’š " " From (1) 𝒅𝒛/π’…π’š = 1 dz = dy Integrating on both sides ∫1▒𝑑𝑧 = ∫1▒𝑑𝑦 z = y + c Putting 𝑒^(π‘₯/𝑦) = z 𝒆^(𝒙/π’š) = y + c

Ask a doubt
Davneet Singh's photo - Co-founder, Teachoo

Made by

Davneet Singh

Davneet Singh has done his B.Tech from Indian Institute of Technology, Kanpur. He has been teaching from the past 13 years. He provides courses for Maths, Science, Social Science, Physics, Chemistry, Computer Science at Teachoo.